2015
DOI: 10.1098/rsbl.2015.0773
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the avian song system in reproductive behaviour

Abstract: The song system of songbirds consists of an interconnected set of forebrain nuclei that has traditionally been regarded as dedicated to the learning and production of song. Here, however, we suggest that the song system could also influence muscles used in reproductive behaviour, such as the cloacal sphincter muscle. We show that the same medullary nucleus, retroambigualis (RAm), that projects upon spinal motoneurons innervating expiratory muscles (which provide the pressure head for vocalization) and upon voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Findings from this study (bold arrows) demonstrate that in females CM projects to the CSt ( n = 12), AIV ( n = 20), RA ( n = 15) and is reciprocally interconnected with NC ( n = 22). Results from previous work show that neurons in the female RA projects to the midbrain structure DM, which then projects to the brain stem nucleus RAm that then innervates motor neurons that control the expiratory muscles and muscles that control the cloaca (Wild & Botelho, ). A connection between AIV and dopaminergic regions in the midbrain (VTA/SNc, dotted arrow) is known to be present in males and is also shown here (Mandelblat‐Cerf et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from this study (bold arrows) demonstrate that in females CM projects to the CSt ( n = 12), AIV ( n = 20), RA ( n = 15) and is reciprocally interconnected with NC ( n = 22). Results from previous work show that neurons in the female RA projects to the midbrain structure DM, which then projects to the brain stem nucleus RAm that then innervates motor neurons that control the expiratory muscles and muscles that control the cloaca (Wild & Botelho, ). A connection between AIV and dopaminergic regions in the midbrain (VTA/SNc, dotted arrow) is known to be present in males and is also shown here (Mandelblat‐Cerf et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to hormonal control of CSD expression, the second route through which CM may influence courtship behavior involves innervation of the muscles that control the cloaca, a reproductive organ where contact with the male occurs. Tract‐tracing in female canaries has revealed that DM projects to a medullary respiratory center (nucleus retroambigualis, RAm) which in turn projects to spinal motor neurons that control the muscles in the cloaca (Wild & Botelho, ). Our results build on those data, providing an additional upstream link through which song perception may shape this circuit and the associated copulatory behaviors: CM→RA→DM→RAm→cloacal motor neurons (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…A well‐studied example is nucleus robustus arcopallialis (RA), a prominent vocal arcopallial nucleus in songbirds. RA receives projections from other pallial vocal areas, projects to vocal and respiratory centers in the midbrain and medulla, and plays key roles in the encoding and expression of learned vocalizations (Hahnloser, Kozhevnikov, & Fee, ; Long & Fee, ; Nottebohm et al, ; Nottebohm, Kelley, & Paton, ; Spiro, Dalva, & Mooney, ; Vicario, ; Wild, ; Wild & Botelho, ; Wild, Williams, & Suthers, ). Analogous nuclei are present in the other bird groups that evolved vocal learning (caudal part of the anterior arcopallium [AAc] in parrots and VA in hummingbirds; Brauth, Heaton, Shea, Durand, & Hall, ; Durand, Heaton, Amateau, & Brauth, ; Gahr, ; Jarvis & Mello, ; Jarvis et al, ), but seem absent in birds that lack this behavioral trait (Kroodsma & Konishi, ; Saldanha, Schultz, London, & Schlinger, , but also see Liu, Wada, Jarvis, & Nottebohm, ; de Lima et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a role for female RA in the control of vocalizations, retrograde labeling experiments in female zebra finches demonstrate descending connectivity from RA to the vocal hindbrain (Johnson & Sellix, ). Interestingly, experiments in a related species (canary) suggest the descending connectivity of RA may also influence female copulatory solicitation displays (CSDs) via disynaptic control of spinal motoneuron pools (Wild & Botelho, ). These data lead to the view that HVC and RA may be a part of a more general network that controls courtship and reproductive behavior (including learned song and CSDs) in both sexes (reviewed by Perkes et al, ).…”
Section: Discussionmentioning
confidence: 99%